Iridoids and lignans from Valeriana officinalis L. and their cytotoxic activities. (June 2022) - Zhang, Dongdong; Zhang, Zilong; Wu, Guoqing; Sun, Yu; Jiang, Yi; Zhang, Huawei; Wang, Wei; Song, Xiaomei; Li, Yuze
Abstract: Two new iridoids (1 and 2 ), one new lignan (3 ) together with one known iridoid (4 ) and twelve known lignans (5 －16 ) were obtained from the roots of Valeriana officinalis L. ( V. officinalis ). The structures were determined using IR, MS, 1 D and 2 D NMR spectroscopy and the absolute configurations of the new structures were deduced by ECD experiments. All of the isolated compounds were assayed for their cytotoxic activities against three tumour cell lines (A549, HCT116 and SW620) and the results showed that compounds 9 and 10 showed cytotoxicities against A549 cells, compounds 9 and 11 showed cytotoxicities against SW620 cells and compound 10 showed cytotoxicities against HCT116 cells. Graphical Abstract: ga1 Highlights: Two new iridoids and one new lignan from the roots of Valeriana officinalis L. The structures were elucidated by spectroscopic analysis and chemical evidence. The cytotoxic activities against three tumour cell lines (A549, HCT116 and SW620) for all the compounds were studied.